Effects of re-curing on microstructure of concrete after high temperature exposure - Akca, Abdullah Huzeyfe; Ozyurt, Nilufer (ELSEVIER SCI LTD, 2018)
Concrete contains many phases such as ettringite, portlandite, C-S-H etc. which undergo phase changes by forming some active products such as lime and calcium silicates during heating. These new active phases give reactions with water and carbon dioxide in air and affect the residual properties of concrete after subsequent days of cooling. In order to understand better these phase changes and their effects on residual properties, 3 different types of concrete were produced depending on mineral admixture type. Concrete specimens were heated to 1000 degrees C and one face heating procedure was applied in the furnace. Then concrete specimens were subjected to air and water re-curing processes. Microstructural investigations XRD, TGA and SEM/EDX were conducted on the samples obtained from concrete specimens. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: High temperature; Fiber reinforced concrete; Recovery; Deterioration; Microstructure; FIRE-DAMAGED CONCRETE; HIGH-STRENGTH CONCRETE; CEMENT PASTE; ELEVATED-TEMPERATURES; COMPRESSIVE STRENGTH; PERFORMANCE; BEHAVIOR; SLAG; Construction & Building Technology; Engineering; Materials Science